Dampak Pelabuhan Perikanan Samudera Kendari terhadap Kondisi Sosial Ekonomi Masyarakat Nelayan di Kecamatan Abeli Kota Kendari - Silviana, Silviana; Limi, Muhammad Aswar (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
This study aims to determine how the impact of the Kendari Sea Fisheries Port on the socio-economic conditions of the fishing community in the Abeli District. The determination of the study area was carried out by census sampling with 64 respondents. The method of data analysis uses descriptive qualitative analysis which consists of describing the facts, nature, and relationships between the phenomena encountered. Respondents' assessment of indicators measured with 5 Likert scales and the results of the Likert scale tabulation were analyzed using class intervals and interpretation in the form of a percent (%). The results of the study note that the social impact of the existence of the Kendari ocean fishery port has an influence on the level of education and health level of fishermen and their family members as well as the absence of social change and social interaction between fishing communities while the economic impact of the existence of the Kendari ocean fishery port has an influence on employment opportunities in industries that there is a PPS in Kendari, the opportunity to try with the opening of business opportunities that can become opportunities for trading activities so as to increase the income of fishermen communities.